Direitos políticos fundamentais: rediscussão dos direitos à informação e de representação política - Oliveira, Roberto Martins de (2009)
The present dissertation makes an analysis about the democracy crisis in the liquid modernity, accordingly to the theories proposed for Zigmunt Bauman, Antônio Gramsci and João Pissara Esteves. The main objective to be reached, on this essay, is to propose a reform of the political representation rights, in Brazil, in order to consolidate the participative democracy. Based on the assumption that the unsicherheit of the liquid times contributes to weaken the representation rights, it is argued the reconstruction of the democracy, aiming to turn effective the sovereign power of the people. The philosophy of praxis serves as methodological inspiration, with the retaking of the concepts by hegemony and civil society, searching the full development of civil society’s ability to regulate itself. The efficacy for this purpose depends upon great regulation of the mass media, aiming the protection of fairness information right because some segments of the media are prone to simulate reality, with nondeclared ideological purposes, but, indeed, present. It depends too on new regulations about the party and electoral systems, and, mainly, on the radicalization of the normative institutes about the direct exercise of sovereignty by the people, which are enclosed in article 14º of the Constitution of the Federative Republic of Brazil: referendum, plebiscite and popular initiatives.